2022
DOI: 10.1093/pm/pnac035
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Temperature Rise After Sympathetic Block and Pain Relief in Patients with Complex Regional Pain Syndrome

Abstract: Objective Determine the correlation between post-sympathetic block pain temperature change, and immediate and intermediate-term pain relief. Design Retrospective analysis Setting Academic setting Subjects 79 pts with CRPS who underwent sympathetic block. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The trunk had a single sympathetic ganglion at each vertebral level on each side of the spine. The location of each sympathetic ganglion was not precisely the same at each vertebral level, and it differed among cadavers owing to the normal anatomical variability demonstrated by other authors (Samen et al, 2022; Van Eijs et al, 2012). Our findings agree with Datta and Pai (Datta & Pai, 2004).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The trunk had a single sympathetic ganglion at each vertebral level on each side of the spine. The location of each sympathetic ganglion was not precisely the same at each vertebral level, and it differed among cadavers owing to the normal anatomical variability demonstrated by other authors (Samen et al, 2022; Van Eijs et al, 2012). Our findings agree with Datta and Pai (Datta & Pai, 2004).…”
Section: Discussionmentioning
confidence: 89%
“…More accurate direct measurements of sympathetic blockades, such as skin temperature and regional tissue blood flow change pre‐ and post‐block, would be preferable measurements. Some authors include skin temperature measurement pre‐ and post‐block as a guide to block success (Meier et al, 2009; Van Eijs et al, 2012), even though skin temperature increase after sympathetic block in these studies evidently did not correlate with pain (Samen et al, 2022; Van Eijs et al, 2012). Nevertheless, we propose that the apparent high failure rate stems from anatomical and pathophysiological issues.…”
Section: Introductionmentioning
confidence: 99%
“…Some retrospective studies have found no correlation between pain relief following a sympathetic block and temperature increase in patients with CRPS. These studies examined the relationship between temperature increase and pain reduction immediately after a single LSGB, stellate ganglion block, or LSGN in patients with CRPS 12 , 26 . The results indicated a very weak correlation between temperature rise and immediate pain relief following the procedure, despite patients with larger temperature increases experiencing greater immediate pain relief.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, Tran et al 37 described a direct relationship between the temperature increase and the relief of pain and allodynia. However, other authors deny this correlation 3,19,31,38 . Kim et al 14 validated the accuracy of thermography to confirm the success of LSBs.…”
Section: Discussionmentioning
confidence: 99%
“…However, other authors deny this correlation. 3,19,31,38 Kim et al 14 validated the accuracy of thermography to confirm the success of LSBs. In a preliminary study published by Cañada-Soriano et al, 44 LSBs were performed for the treatment of CRPS in lower limbs in 13 patients under radioscopic control and confirmation of block success by thermography.…”
Section: Discussionmentioning
confidence: 99%